Socioeconomic situation and well-being of extractivist women on Marajó Island, Brazil (Research, Society and Development, 2020)
This research was carried out with andiroba oil extractors associated with the Ecological Cooperative of Extractive Women on the island of Marajó-PA, in order to determine the socioeconomic profile of these workers and their satisfaction with the attributes of this cooperative system. The sample consisted of 26 women from different locations on Marajó Island: Ponta de Pedras, Jagarajó and Marajó Ité. Data collection was carried out using structured forms, which were subsequently submitted to descriptive statistics and whose variables were used to calculate the Cooperative Evaluation Index (IAC). The results indicated that these women, in their majority, have low education. Artisanal fishing is practiced in parallel to the traditional oil extraction work by a large part of the workers who, together with the Bolsa Família Program, contribute to the supplement of a monthly income of 1 minimum wage and, even, these women expressed interest in free professional courses. No cooperative receives social benefits from that cooperative. In addition to the fact that the local infrastructure, the organization of the cooperative, the income obtained from the sale of vegetable oil and the leadership's performance cause dissatisfaction in these cooperative members, while the extracted andiroba oil was positively evaluated, imprinting this reasonable cooperative system, according to the calculated IAC. In addition, these women have shown that it is possible to earn income from forest products, but they need public policies that ensure minimum working conditions.